(untitled) (Jurnal Pertanian Terpadu, 2025)
This study aims to evaluate the effectiveness of dry powder formulations of Metarhizium anisopliae against the cumulative mortality and progression of infection symptoms in Cylas formicarius after different storage durations under tropical room conditions. The bioassay was conducted using six storage periods (1, 2, 3, 4, 5, and 6 months) and assessed for cumulative mortality and visible infection symptoms over 120 hours post-inoculation. The results showed that the formulation stored for 1 month (P1) produced the highest cumulative mortality of 10% within 120 hours, followed by P2 (7%), P3 (5%), P4 (4%), P5 (3%), and P6 (2%). The progression of infection symptoms followed a typical entomopathogenic fungal infection pattern, beginning with no changes at 0–24 hours, color changes at 24–48 hours, softening of the body at 48–72 hours, blackened and fragile integument at 72–96 hours, and culminating in complete mummification at 96–120 hours. Dual-axis plots revealed a strong correlation between infection symptom progression and mortality, with a significant mortality increase occurring during the blackened to mummification phase. These findings confirm that storage duration influences the viability and pathogenicity of M. anisopliae formulations, affecting infection kinetics and mortality levels in C. formicarius. This study supports the recommendation of using dry formulations stored for no more than 1–2 months to maintain optimal biocontrol efficacy.